Business Network Analysis in Increasing Sales Volume in Rengginang Cililin WestBandung District - Ramkutih, Pingky Abda; Yuliana, Lia; Marselina, Resya Dwi (Jurnal Computech & Bisnis (e-journal), 2024)
This study aims to examine the business network's impact on the sales volume of rice crackers at a specific production house in Cililin. The study utilizes a qualitative research methodology with a descriptive model, including interviews, observations, and documentation as research methods. The research findings indicate that a rice cracker production facility in Cililin has established a robust production network, with several suppliers providing raw materials. Additionally, the facility has developed a marketing network by actively participating in the trader community in West Bandung. Furthermore, the facility has formed cooperative partnerships with different supplier stores to facilitate distribution. The rice cracker production plant in Cililin has effectively enhanced its annual sales volume through its established business network while selling items exclusively within the local vicinity. Hence, it is recommended that the production company in Cililin enhance its commercial network to broaden prospects, resulting in a surge in sales volume and profits. This entails expanding corporate networking to expand the market reach and optimizing management systems for a more streamlined firm operation.